Role of primary care physician in health promotion and education - Abdullah, Marwah Yakoop; Alshehri, Samaher Ali; Mahnashi, Haneen Ali; Alshahrani, Saeed Saad; Alkhaldi, Shahad Saad; Alshammari, Saad Munawwikh; Alotaibi, Renad Sultan; Qutub, Razan Muneer; Jamhan, Abdullah Yahya; Alhussain, Sarah Abbas; Abdulqader, Ahmad Khaled; Binmahri, Moaid Khalid (International Journal Of Community Medicine And Public Health, 2022)
Undisputedly, healthy behaviours and lifestyles have a positive impact on health outcomes, and its individual, social, environmental, and cultural determinants are well understood. Primary care physicians can effectively intervene with patients to encourage healthy behaviour through numerous chances. Regular clinical practice includes health promotion as a necessary element. Health systems can support a person's health requirements through primary health care, including illness prevention, treatment, palliative care, and more. This approach also guarantees that the delivery of healthcare is centred on patients' needs and supports their preferences. Regular care must incorporate health promotion strategies if the healthcare system is to be effective. Giving individuals the information, they need to improve and take better control of their health is the goal of health promotion. Primary care physicians are the immediate contact with the community which makes them the ideal candidates for health promotion and education. The purpose of this research is to review the available information about the role of primary care physician in health promotion and education. Health promotion and education is necessary for the prevention of diseases as it aids in educating population regarding diseases and risk factors. Also, because of its accessibility to care and continuity of treatment, primary healthcare is in a prime position to potentially intervene to modify unhealthy habits. Primary care physicians being first line of contact plays a key role in this regard. Although further research is needed for the implementation of health promotion and education strategies by primary care physicians.